The voyage of Captain Don Felipe González in the ship of the line San Lorenzo, with the Frigate Santa Rosalia in company, to Easter Island in 1770-1 : preceded by an extract from Mynheer Jacob Roggeveen's official log of his discovery and visit to Easter Island in 1722 /: preceded by an extract from Mynheer Jacob Roggeveen's official log of his discovery and visit to Easter Island in 1722. (2017) - González de Haedo, Felipe, 1714-1792; Roggeveen, Jacob, 1659-1729
No abstract available